2012
DOI: 10.1371/journal.pone.0036322
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the Organization of Locomotor and Exploratory Behaviors in Bile Duct-Ligated Rats

Abstract: Hepatic encephalopathy (HE) arises from acute or chronic liver diseases and leads to several problems, including motor impairment. Animal models of chronic liver disease have extensively investigated the mechanisms of this disease. Impairment of locomotor activity has been described in different rat models. However, these studies are controversial and the majority has primarily analyzed activity parameters. Therefore, the aim of the present study was to evaluate locomotor and exploratory behavior in bile duct-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 31 publications
4
16
0
Order By: Relevance
“…One may also speculate that A B C D chronic hyperammonemia from birth in Glul fl/fl × Alb-Cre + mice may trigger so far unknown adaptations that are not present in other experimental settings or in patients with liver failure. However, that chronic hyperammonemia in Glul fl/fl × Alb-Cre + mice does not promote anxious behavior is consistent with findings obtained from bile duct-ligated rats (47) or rats after portocaval anastomosis (50). Interestingly, oxidative stress markers were not elevated in the piriform cortex of liver-specific GS KO mice.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One may also speculate that A B C D chronic hyperammonemia from birth in Glul fl/fl × Alb-Cre + mice may trigger so far unknown adaptations that are not present in other experimental settings or in patients with liver failure. However, that chronic hyperammonemia in Glul fl/fl × Alb-Cre + mice does not promote anxious behavior is consistent with findings obtained from bile duct-ligated rats (47) or rats after portocaval anastomosis (50). Interestingly, oxidative stress markers were not elevated in the piriform cortex of liver-specific GS KO mice.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, in the cerebellum of mice lacking hepatic GS, we identified exceptionally high levels of oxidized RNA in Purkinje cells, which critically control motor functions (30). In line with deranged cerebral motor control, the present study identified increased locomotion in mice lacking hepatic GS with liver damage and/or cholestasis due to bile duct ligation (47,48), portocaval shunting (49), or portal vein ligation (14). This difference may suggest a role of impaired liver metabolism other than ammonia detoxification for decreased locomotion in these HE animal models.…”
Section: Discussionsupporting
confidence: 79%
“…This progressive yet incomplete osmotic compensation is probably the underlying cause of the observed minimal brain edema associated with chronic HE, as previously shown Bosoi et al 2014). Moreover these changes go along with the appearance of the neurological signs towards the end stage of the disease, as demonstrated by the decrease in locomotor activity in the Open Field task using the same animal model (Leke et al 2012;Rackayova et al 2015). Although these findings are not novel, they show that the changes underlying the characteristic high Gln signature of HE occur progressively over the course of time.…”
Section: Discussionmentioning
confidence: 56%
“…These models, developed to mimic type C HE, try to reproduce the clinical characteristics of chronic cirrhosis and its cognitive and motor symptoms, and they require obstruction of the bile duct [12][13][14][15][16] or the administration of hepatotoxins, such as carbon tetrachloride or thioacetamide (TAA) [17]. Several studies have reported that the chronic oral administration of TAA causes an impairment in associative learning and spatial memory in rats [18][19][20][21][22].…”
mentioning
confidence: 99%